Social and Cultural Problems of Bioethics in Modern Times - Karimovna, Mamajonova Gulnoza (International Journal of Psychosocial Rehabilitation, 2020)
Bioethics is one of the bio-social disciplines that emerged within the boundaries of the natural and social sciences during the time when natural sciences began to evaluate their social effectiveness. In this article, bioethics is discussed as a cultural system. Socio-cultural problems of bioethics are conceptually analyzed.